Le système financier montréalais : quelques lacunes - Briant, Peter; Whittaker, Gary (L'Actualité économique, 1974)
AbstractThe objective of this paper is to describe some important gaps in the Montreal financial community. These gaps are examined in turn from the points of view of the small investor and the small business.The investor with 50,000 dollars to invest does not currently receive unpartial financial advice from existing financial institutions, due to the latters' roles as financial intermediaries as well as advisors. There is a need for a government supported agency which would act as a buffer between investors and intermediaries, would buy the services of the professional consultants, and then relay this expert advice back to the investor.The gaps concerning the equity financing of small new business are detected by means of a survey of Montreal small firms, the results of which indicate that venture capital does not satisfy the equity needs of new firms in stage zero of development. Interviews with five venture capital firms confirm these observations and further classify the gaps along five dimensions, leading to five types of gaps: stage of development, industry, location, information and communication. Here too, a public agency could successfully fill these gaps of venture capital. An example of the action of such an agency to help start a new business is described and serves as conclusion.